One-Dimensional Modeling Studies of the Gaseous Electronics Conference RF Reference Cell - Govindan, T. R. (J Res Natl Inst Stand Technol, 1995)
A review of the one-dimensional modeling studies in the literature of the Gaseous Electronics Conference (GEC) reference plasma reactor is presented. Most of the studies are based on the fluid model description of the discharge and some utilize hybrid fluid-kinetic schemes. Both models are discussed here briefly. The models provide a basic understanding of the discharge mechanisms and reproduce several critical discharge features observed experimentally.